ISLAM LOKAL” PERSPEKTIF HISTORIS DAN POLITIK” Memahami Narasi Islam Maluku dalam Konstruksi Poskolonial - Abdul Manaf Tubaka Sittin Masawoy (IAIN Ambon, 2018)
This research seeks to reveal how local Muslims in Maluku historically and politically dominated by traditional Sufic Islam. In that context, this study also want to describe the local Muslim in their religious relations in space tersimbolkan Moluccan culture in the local wisdom Pela (PG) and Gandong, Larwul Ngabal (LN), Aini Ain (AA), and others. Local Muslims with the typology that Sufic Traditional forming character akomudatif against local kearfian. But at the same time also resistant to mengendepankan attitude of religious fanaticism. In such form, Islam is like a local in Maluku two coins which Idenitas Islam and cultural identity can not be separated from each other, but at the same time, tensions Identity religion also occur as forms of currency pieces back to back with each other. Historically, local Islamic formed in power between the competing power of the power system of the Islamic empire in the Moluccas by colonial powers which also carries a religious mission and then gave birth to self-identification between